Utilização de resíduos de Pinus spp. na produção de blocos de concreto para alvenaria de vedação - Oliveira, Marilucia Silveira (2020)
The objective of this work was to investigated the use of Pínus wood spp. Residues, as lignocellulosic aggregate, in substitution of the mineral aggregate in the production of cement-wood composites that served as the basis for the production of concrete blocks. The research was divided into two stages, firstly the production of cementwood composites and then the production of concrete blocks. In the first, 15 5x10 cm cylindrical specimens were produced for nine concrete traces, using a vibration compression system, varying the substitution content of mineral aggregate by the equivalent volume of Pínus wood spp. The physical and mechanical characteristics, compressive strength, specific mass, water absorption and voids index of the sample sets were evaluated. A second step consisted in the evaluation of the replacement adaptation of the wood residue, as well as in the analysis of the most favorable trace for the mixtures in order to reach the compression strength at 28 days of 3,0 MPa, compiled by NBR 6136 (ABNT, 2016) for class C blocks with or without structural function, based on the results achieved in the first stage, ending with the production of 24 concrete blocks measuring 14 x 19 x 39 cm in line 1: 8 with 25,0% conversion wood waste, 12 reference blocks, without waste, and 12 blocks with waste wood. The tests of resistance to compression, specific mass, water absorption, voids index, dimensional analysis and liquid area were carried out. The induced results that the concrete blocks obtain with the wood residues, in the studied composition, meet the normative requirements, as well as the reduction of 11,0% in the specific mass in comparison with the blocks collected from the wood residue, and still provided a cement: wood proportion of 15,0%. These results indicate the viability of using wood waste in the production of concrete blocks, class C, for masonry with or without structural function.